1996
DOI: 10.1083/jcb.133.5.1083
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of I kappa B-alpha phosphorylation and degradation and subsequent NF-kappa B activation by glutathione peroxidase overexpression.

Abstract: Abstract. We report here that both KB-dependent transactivation of a reporter gene and NF-KB activation in response to tumor necrosis factor (TNFc 0 or H202 treatments are deficient in human T47D cell transfectants that overexpress seleno-glutathione peroxidase (GSHPx). These cells feature low reactive oxygen species (ROS) levels and decreased intracellular ROS burst in response to TNFot treatment. Decreased ROS levels and NF-KB activation were likely to result from GSHPx increment since these phenomena were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
1
3

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(150 citation statements)
references
References 81 publications
11
134
1
3
Order By: Relevance
“…It is thus extremely unlikely that PHGPx, which is less abundant than any of its congeners, is of vital importance because of its antioxidant potential. Modulation of cytokine responses, as reported for gpx-4 overexpression, cannot likely be reconciled with embryogenesis either, because it has been similarly reported for GPx-1 (42), and needless to say, the role of PHGPx as a structural protein of spermatozoa is irrelevant to embryonic development. Rather a unique role of PHGPx in cellular differentiation would be compatible with the outcome of the reverse genetics approach.…”
Section: Discussionmentioning
confidence: 94%
“…It is thus extremely unlikely that PHGPx, which is less abundant than any of its congeners, is of vital importance because of its antioxidant potential. Modulation of cytokine responses, as reported for gpx-4 overexpression, cannot likely be reconciled with embryogenesis either, because it has been similarly reported for GPx-1 (42), and needless to say, the role of PHGPx as a structural protein of spermatozoa is irrelevant to embryonic development. Rather a unique role of PHGPx in cellular differentiation would be compatible with the outcome of the reverse genetics approach.…”
Section: Discussionmentioning
confidence: 94%
“…The target cellular mechanisms protected in the synaptic transmission and the LTP signaling pathways and machinery remain to be identified. Candidate mechanisms may include prevention of signaling interference involving kinase activation (or tyrosine phosphatase inhibition by free radicals) that may culminate, for example, in the inhibition of both I B phosphorylation and NF B activation (35); inhibition of peroxide-mediated activation of phospholipase A2 (36); and prevention of oxygen free radicalmediated damage to glutamate-uptake systems (37). Hypoxic insults were reported to transiently augment the extracellular concentration of glutamate (38).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies of oxidized OxyR revealed that the transcriptional factor is activated through the formation of a disulfide bond and is deactivated by reduction with glutaredoxin (Zheng et al, 1998). N F-κB was the first eukaryotic transcription factor shown to respond directly to oxidative stress Baeuerle and Baltimore, 1996;Kretz-Remy et al, 1996). The transactivator plays a crucial role in the regulation of numerous genes involved in immune and inflammatory processes.…”
Section: Production Of H 2 O 2 In Response To Receptor Stimulation Inmentioning
confidence: 99%